Molecular systematics of some bifurcate hairy sections in Astragalus L. (Fabaceae) as inferred from nuclear and chloroplast DNA sequences (Bangladesh Journal of Plant Taxonomy, 2016)
In this study, 38 species belonging to some bifurcate hairy sections of Astragalus L. were analyzed phylogenetically, using nuclear and plastid DNA sequences. Based on our results, Astragalus sect. Dissitiflori DC. with the inclusion of the members of section Erioceras Bunge, formed a monophyletic group. The members of sect. Ornithopodium Bunge and Onobrychoidei DC. were located together within a highly supported monophyletic clade, apart from other sections studied, on the basis of the present molecular data.The positioning of the enigmatic, recently established species, A. juladakensis Maassoumi, within the sect. Dissitiflori was verified. In addition, our results showed that A. pravitzii Podl., which had been already transferred to sect. Ornithopodium, belongs to the section Dissitiflori.Bangladesh J. Plant Taxon. 23(2): 223-235, 2016 (December)